2021
DOI: 10.6018/sportk.489161
|View full text |Cite
|
Sign up to set email alerts
|

Does adding extracorporeal shock wave therapy to postural correction exercises improve pain and functional disability in postpartum sacroiliac joint pain? A randomized controlled trial

Abstract: El objetivo de este estudio fue examinar el resultado de la terapia de ondas de choque extracorpóreas (TOCH) en mujeres con dolor en la articulación sacroilíaca posparto. Cuarenta mujeres primigrávidas (seis semanas después del parto) con dolor sacroilíaco participaron en este estudio. Fueron asignadas al azar a los grupos A y B. El grupo A fue tratado mediante TOCH, además de ejercicios de corrección postural y ejercicios de inclinación pélvica posterior. El grupo B fue tratado únicamente con el mismo program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…These findings could be reinforced by Elhosary et al [11] , who found that 8-week of combined application of shockwave therapy and a program of posture correction exercise had superior effects on lowering VAS scores of sacroiliac pain and enhancing the function of postnatal women with sacroiliac joint pain than did the exercise program alone. Additionally, Saleh et al [24] reported that the addition of shockwave therapy to Mulligan mobilization for 8 weeks resulted in significantly greater PPT increase, ODI scores reduction, and mobility improvement when compared to only Mulligan mobilization in female and males patients with sacroiliac joint dysfunction.…”
Section: Group (B) (N = 15) P-value* Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…These findings could be reinforced by Elhosary et al [11] , who found that 8-week of combined application of shockwave therapy and a program of posture correction exercise had superior effects on lowering VAS scores of sacroiliac pain and enhancing the function of postnatal women with sacroiliac joint pain than did the exercise program alone. Additionally, Saleh et al [24] reported that the addition of shockwave therapy to Mulligan mobilization for 8 weeks resulted in significantly greater PPT increase, ODI scores reduction, and mobility improvement when compared to only Mulligan mobilization in female and males patients with sacroiliac joint dysfunction.…”
Section: Group (B) (N = 15) P-value* Discussionmentioning
confidence: 93%
“…The probe was moved upward and downward along the posterior sacroiliac joint line while being held perpendicular to the joint line (Figure 2). The parameters were 2400 pulses, frequency of 8 Hz, and an energy density of 0.11 mJ/mm 2 [11] .…”
Section: Shockwave Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…A higher score indicates more functional limitation due to back problems. (3) Patients function level by using back pain function scale (BPFS) [18] : it consists of 12 objects of daily activities with 5 different answers. Patient response to each item was reported by each participant conferring to her capability to apply this activity.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…8 Moreover, pain can lead to insomnia and problemsolving deficits, 9 and these conditions may increase risk for suicidality. 10,11 Pain may be an important risk factor for suicidality especially in older adults in LMICs as studies have shown a trend toward increasing prevalence of pain with increasing age with the highest prevalence being observed among older adults, [12][13][14] while the prevalence of chronic pain has been reported to be particularly high in LMICs. 15 Cancer pain, acute pain, and chronic non-cancer pain all contribute to a large burden of pain in LMICs, which is frequently underdiagnosed and undertreated.…”
Section: Introductionmentioning
confidence: 99%